Effect of UV Aging on Physical Properties of Vulcanized Rubber with the Addition of Reclaimed Rubber - Muh. Wahyu Syabani; Yuli Suwarno; Mertza Fitra Agustian (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
Rubber solid waste amount increased continuosly and caused environmental problem since it is very difficult to be naturally degraded. Therefore, the interest of using rubber waste as raw material for new rubber product is increased. Reclaimed rubber can be used as filler aditif for rubber processing. The aim of this research was to study the effect of UV aging on the rubber product as the reclaimed filler added. The mixing of the rubber and the additives used the kneader and open mill. The vulcanization process was done by hydraulic press. In this research, the reclaimed rubber addition was varied as follows: 12,5; 37,5 and 62,5 phr. The products quality differences before and after the UV aging evaluated using physical tests. The result of FTIR showed that the polymer chain were broken by ultraviolet radiation. The physical test gives result that the hardness and tensile strength decreased, but the elongation is increased after UV aging.